Greenhouse Gas Emission Estimation for Selected Crops and Rice Cultivation in Urban and Non-Urban Areas of Sarawak - Bahrum N.A.; Malek M.A.; Tan C.S. (EDP Sciences, 2023)
Biomass; Carbon; Crops; Cultivation; Environmental engineering; Forestry; Land use; Uncertainty analysis; Biomass and soils; Carbon loss; GHG emission; Organic soil; Rice cultivation; Sarawak; Urban areas; Greenhouse gases